What Does the Literature Tell Us? Reviewing Literature Reviews on Information Behavior. Issue 1 (13th October 2021) - Zhang, Xiaoqian; Bartlett, Joan C.
ABSTRACT: Many reviews on information behavior have been published to date, however little research has been done to understand these reviews. To fill this gap, this poster reviewed 96 literature reviews in this field. The preliminary analysis uncovers several characteristics of literature reviews on information behavior: (1) these reviews have discussed two transformations in the history of information behavior; (2) current literature reviews focus on specialized areas of information behavior; (3) literature reviews have highlighted different issues in information behavior research, such as the quality of information and the practical contributions of research; (4) literature reviews keep summarizing and developing theories and models of information behavior. This preliminary analysis provides an overview of 30 years of literature reviews, showing what existing literature reviews have done. It identifies trends in information behavior research and may inspire what kinds of literature reviews are needed in the future.